Experimental and theoretical studies of hexagonal boron nitride single crystal growth - Liu, Song (Kansas State University, 2018)
Hexagonal boron nitride (hBN) has recently been envisioned for electronic, optoelectronic, and nanophotonic applications due to its strong anisotropy and unique properties. To realize these applications, the ability to synthesize single crystals with large size and low defect density is required. Furthermore, a detailed mechanistic understanding of hBN growth process is helpful for understanding and optimizing the synthesis technique for high quality crystals. In this dissertation, the production of large-scale, high-quality hBN single crystals via precipitation from metal solvents, including Ni-Cr and Fe-Cr, was demonstrated. The use of Fe-Cr mixture provides a lower cost alternative to the more common Ni-Cr solvent for growing comparable crystals. The clear and colorless crystals have a maximum domain size of around 2 mm and a thickness of around 200 μm. Detailed characterizations demonstrated that the crystals produced are pure hBN phase, with low defect and residual impurity concentrations. The temperature-dependent optical response of excitons showed that the exciton-phonon interaction in bulk hBN is in the strong-coupling regime. A new growth method for monoisotopic hBN single crystals, i.e. h¹⁰BN and h¹¹BN, was developed, by which hBN single crystals were grown using a Ni-Cr solvent and pure boron and nitrogen sources at atmospheric pressure. The chemical bonding analysis revealed that the B-N bond in h¹¹BN is slightly stronger than that in h¹⁰BN. The polariton lifetime in our monoisotopic hBN samples increases threefold over the naturally abundant hBN, and the isotopic substitution changes the electron density distribution and the energy bandgap of hBN. The ability to produce crystals in this manner opens the door to isotopically engineering the properties and performance of hBN devices. Atomistic-scale insights into the growth of hBN were obtained from multiscale modeling combining density functional theory (DFT) and reactive molecular dynamics (rMD). The energetics and kinetics of BN species on Ni(111) and Ni(211) surfaces were calculated by DFT. These DFT calculations data were subsequently used to generate a classical description of the Ni-B and Ni-N pair interactions within the formulation of the reactive force field, i.e., ReaxFF. MD simulations under the newly developed potential helped reveal the elementary nucleation and growth process of an hBN monolayer - nucleation initiates from the growth of linear BN chains, which further evolve into branched and then hexagonal lattices. In the end, molecular dynamics simulations demonstrated that the thermodynamic preference of hBN geometries varying from triangle to hexagonal can be tuned by B to N molar ratios, and gas phase N₂ partial pressure, which is also supported by quantum mechanics calculations. The modeling confirms that the nitrogen species indeed plays an important role in dictating sizes and edge terminations of hBN sheets.
Keywords: Hexagonal Boron Nitride; Crystal Growth; Semiconductor; 2D Materials; DFT; Molecular Dynamics